Priority directions of development of decentralization of power - Dvihun, Alla (Management and Entrepreneurship: Trends of Development, 2018)
The urgency of the theme under study is due to the need to simplify the structure of local governance, to ensure close ties with civil society and to achieve transparency in the adoption of management decisions, and increase the level of responsibility to the territorial community. The research is aimed at solving the problems of financial provision of territories development.Findings. The concept of decentralization of power, in particular budget decentralization, is considered. It was established that the interconnection of legislative changes in the Tax and Budget Codes contributed to the transformation of local budgets into an effective instrument of socioeconomic development of administrative and territorial units. The advantages of budget decentralization are revealed. The development of the processes of the formation of associations of territorial communities (ATC) is explored.Priorities of the changes introduced are the extension of the rights of local self-government authorities in decision-making and giving them full budgetary autonomy in terms of filling their budgets and spending their powers in the light of European experience. The essence of the new mechanism of budgetary regulation is revealed, namely, the system of total balancing of all local budgets is replaced by the system of horizontal equalization of the capacity of administrative-territorial units depending on the level of income per capita. The positive results of the reform of fiscal decentralization are substantiated. The expediency of carrying out calculations of intergovernmental transfers on the basis of consolidated budgets of regions is proved, transferring responsibility for further redistribution of budget funds to regional state administrations. Further directions of the budget decentralization reform in Ukraine are outlined.The scientific significance of the work is to substantiate measures to strengthen the financial basis of local self-government; outlined the priority steps of regional state administrations on the way to solving the urgent problems of implementing the budget decentralization reform. The practice of budget decentralization has proven that it contributes to the growth of the financial potential of the territory, the intensification of investment activity, and the stimulation of entrepreneurial activity, which ultimately strengthens the economic potential and provides a "ground" for growth and development, and therefore the further development of the order of financial and administrative liability for violation by local government of the requirements of budget legislation.